Clinical utility of endoscopic ultrasound‐guided biliary drainage as a rescue of re‐intervention procedure for high‐grade hilar stricture. Issue 1 (January 2017) - Ogura, Takeshi; Onda, Saori; Takagi, Wataru; Sano, Tatsushi; Okuda, Atsushi; Masuda, Daisuke; Yamamoto, Kazuhiro; Miyano, Akira; Kitano, Masayuki; Takeuchi, Toshihisa; Fukunishi, Shinya; Higuchi, Kazuhide
Abstract: Background and Aim: Re‐intervention after stent placement for malignant hepatic hilum obstruction (HBO) is challenging. endoscopic ultrasound‐guided biliary drainage (EUS‐BD) has been developed as an alternative method for failed endoscopic retrograde cholangiopancreatography (ERCP). In this retrospective study, the clinical utility of EUS‐BD as a rescue drainage technique for HBO patients who failed re‐intervention under ERCP guidance was evaluated. Methods: Between April 2012 and August 2015, patients with HBO were enrolled. Patients' characteristics, kinds of metallic stents, configuration of stent placement, overall survival, stent patency, and results of re‐intervention were reviewed, along with the re‐intervention technical success rate. Results: The biliary stricture type was Bismuth type IV in 59% (23/39) and types IIIa and b in 20.5% (8/39) each. Biliary metallic stent placement was bilateral in 38.5% (15/39), and unilateral in 61.5% (24/39). Primary stent dysfunction was observed in 71.8% (28/39) of cases. Planned re‐intervention under ERCP guidance was attempted in 26 patients. The technical success rate was 62% (16/26). For the 10 patients who failed re‐intervention under ERCP guidance, EUS‐BD was planned. The technical success rate was 100% (10/10). The procedure time was 25.8 min. Adverse events were not seen in any patients. Stent patency after re‐intervention was not significantly different between ERCP (165 days) guidance and EUS‐BD (152 days) guidance ( P  = 0.463) Conclusions: In conclusion, EUS‐BD as a re‐intervention method for metallic stent obstruction was safe and feasible. If ERCP was failed, EUS‐BD may be one of option as re‐intervention method for high‐grade hilar stricture.